THE POLYMORPHISM OF Α2B-ADRENERGIC RECEPTOR GENE — A NEW GENETIC MARKER OF THE HEREDITARY SICK SINUS SYNDROME - S. Iu. Nikulina; V. A. Shulman; A. A. Chernova; D. A. Nikulin; M. I. Voevoda; V. N. Maksimov (Рациональная фармакотерапия в кардиологии)
Aim. To study the association of the hereditary sick sinus syndrome (SSS) with gene α2B-adrenergic receptor (ADRA2B) polymorphism.Material and methods. 29 families with hereditary primary SSS from the database of the Chair of Therapy № 1 of Krasnoyarsk State Medical University named after prof. V.F. Voyno-Yasenetsky were included in the study. Group 1 included probands (20 women and 9 men, 58±0.15 y.o.), group 2 – proband relatives of I, II and III degree (65 males and 68 females, 39±0.13 y.o.), group 3 (control) — 89 healthy volunteers. Clinical examination (physical examination, ECG, bicycle ergometry, ECG monitoring, atropine test, electrophysiological study, echocardiography) was performed in all probands and their relatives. The diagnosis of SSS was confirmed by transesophageal left atrium stimulation in 75 individuals. Genotypic examination of gene ADRA2B I/D polymorphism was performed in 213 individuals: 75 SSS-patients, 49 their healthy relatives, 89 healthy volunteers.Results. 3 types of ADRA2B genotypes (II — homozygous wild, ID — heterozygous, DD — homozygous mutant) were founded by allele-specific polymerase chain reaction. Significant prevalence of the homozygous genotype of more rare alleles DD in SSS-patients (28±5.2%) compared to the control group (8.99±3.0%) was found.Conclusion. Study of the genetic marker can be used to identify predisposition to hereditary SSS in the population and individual-family level. SSS due to mutations in genes that regulate cell function of sinus node and the sinoatrial conduct occurs, apparently, extremely rarely.